Improving Higher Order Thinking Skill (Hots) in Early Children Using Picture Story Book - Asyiful Munar; Winarti Winarti; Nai'mah Nai'mah; Dara Gebrina Rezieka; Aknes Aulia (STAI Hubbulwathan Duri, 2022)
Globalization requires many sectors of life to be ready to compete globally. The application of the HOTS approach is considered an effective approach in growing higher order thinking skills based on nature. The writing of this article is to find out the teacher's strategy in developing higher order thinking skills in children at early childhood education institutions. The research method used in this research is descriptive qualitative, data obtained from observations, interviews and documentation with data analysis techniques using triangulation analysis methods. The results showed that children are often seen as weak individuals and have not been able to learn about social issues. The low ability to think in children is caused by the learning process that has not maximized children to think actively and find solutions to every challenge they face. To develop HOTS during the learning process the teacher must provide opportunities for children to be directly involved in every activity as well as questions that can spark children's thinking.